MODE OF DELIVERY IN TERM AND PRETERM TWINS: A REVIEW. (February 2014) - HUI, D.; BARRETT, J. F. R.
<x content-type="archive" xml:space="preserve">Abstract</x> The incidence of twin pregnancy has risen substantially over the past decade, likely largely as a consequence of artificial reproductive technologies. The perennial dilemmas that apply to any singleton delivery, such as intrapartum monitoring and operative interventions are compounded by the presence of the second fetus. There is no doubt that the conduct of a twin delivery remains one of the most challenging events in the daily practice of obstetrics.